Preseason reports of neck pain, dizziness, and headache as risk factors for concussion in male youth ice hockey players - Schneider, K. J.; Meeuwisse, W. H.; Kang, J.; Schneider, G. M.; Emery, C. A. (Clinical Journal of Sport Medicine, 2013)
Objective: The objective of this study was to determine the risk of concussion in youth male hockey players with preseason reports of neck pain, headaches, and/or dizziness.